PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS MODEL LEARNING CYCLE 7E PADA MATERI USAHA DAN ENERGI KELAS X SMA - Munawarah Munawarah; Nur Islami; Muhammad Syafi’i (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: Learning devices are tools or equipment that are used by teachers in carrying learning activities. The learning tools are needed so that learning does not feel monotonous and boring, and can increase the activity of students. The learning tool developed is a learning device based on the Learning Cycle 7E model on work and energy materials for class X senior high school, which consists of a Learning Implementation Plan (RPP), Student Worksheets (LKPD), and Learning Outcomes Tests. The purpose of this study was to design and develop and validate learning tools based on the learning cycle 7E model on work and energy materials. Learning tools are developed using the 4-D model, which consist of define, design, develop and disseminate. However, this development is only carried out until the develop stage. The research instrument used was the form of RPP validation sheets, LKPD and Learning Outcomes Tests which was used by the validator to assess learning tools. The data were analyzed descriptively to determine the validity of the learning device using the Aiken's V formula. The results showed that the validity index value of Aiken's V for RPP was 0.80, the validity index value of Aiken's V for LKPD was 0.83, and the validity index value of Aiken's V for test was learning outcomes was 0.86. Thus, it can be concluded that the learning tool based on the 7E Learning Cycle model is valid and suitable for use in work and energy materials for class X senior high school.Keyword: Learning Devices, Learning Cycle 7E Model, Work and Energy.